The establishment and management of fodder banks - Mohamed-Saleem, M.A. (International Livestock Centre for Africa, 1986)
Presents guidelines for the establishment & management of fodder banks, particularly selection of site, land preparation; sowing & presowing treatment of legumes, seedling establishment and early management. Lists 5 of the factors influencing productivity of fodder banks in the subhumid zone of Nigeria and includes preliminary results of productivity crude protein content, botanical composition and regenerative ability.